Aplicación Web para el almacenamiento, control y distribución de la información de los procesos inmobiliarios del registro de la propiedad municipal de Quevedo - Bravo Coello, Carlos Guillermo (2014)
This paper has developed a web application for storage , control and distribution of information in property processes Registry of the Municipal Property Quevedo. This software processes the property registry of the Municipal Property Quevedo be made more efficient by optimizing the time seeking information. Through the web application administrator and the staff can manage users , customers, properties , commercial properties and commercial properties in society. The web application has been developed following the methodology Dynamic Systems Development Method (DSDM), which is based on the Rapid Application Development (RAD) ,it mean ,you can program the system using any development environment applications and considers the end user as a member of the development team , giving great importance to their opinion. The research method based on the hypothesis has been experimental - explanatory , since its focus is to explain why a phenomenon occurs and under what conditions it occurs , or why two or more variables are related. To test T -Student was used because the time spent in the process of management of both traditional real estate information such as optimized and it is assumed that the data corresponds to a normal function will be compared , since the sample is less thirty people Once built the web application, you can access it through from any host within the Property Registry of the Canton Municipal Quevedo, as this website is only enabled for intranet, using any browser.